Essential Hypertension Is Associated With Changes in Gut Microbial Metabolic Pathways: A Multisite Analysis of Ambulatory Blood Pressure. Issue 3 (2nd August 2021) - Nakai, Michael; Ribeiro, Rosilene V.; Stevens, Bruce R.; Gill, Paul; Muralitharan, Rikeish R.; Yiallourou, Stephanie; Muir, Jane; Carrington, Melinda; Head, Geoffrey A.; Kaye, David M.; Marques, Francine Z.
Abstract : Supplemental Digital Content is available in the text. Abstract : Recent evidence supports a role for the gut microbiota in hypertension, but whether ambulatory blood pressure is associated with gut microbiota and their metabolites remains unclear. We characterized the function of the gut microbiota, their metabolites and receptors in untreated human hypertensive participants in Australian metropolitan and regional areas. Ambulatory blood pressure, fecal microbiome predicted from 16S rRNA gene sequencing, plasma and fecal metabolites called short-chain fatty acid, and expression of their receptors were analyzed in 70 untreated and otherwise healthy participants from metropolitan and regional communities. Most normotensives were female (66%) compared with hypertensives (35%, P <0.01), but there was no difference in age between the groups (59.2±7.7 versus 60.3±6.6 years old). Based on machine learning multivariate covariance analyses of de-noised amplicon sequence variant prevalence data, we determined that there were no significant differences in predicted gut microbiome α- and β-diversity metrics between normotensives versus essential or masked hypertensives. However, select taxa were specific to these groups, notably Acidaminococcus spp ., Eubacterium fissicatena, and Muribaculaceae were higher, while Ruminococcus and Eubacterium eligens were lower in hypertensives. Importantly, normotensive and essential hypertensive cohorts could be differentiated based on gut microbiome gene pathways and metabolites. Specifically, hypertensive participants exhibited higher plasma acetate and butyrate, but their immune cells expressed reduced levels of short-chain fatty acid-activated GPR43 (G-protein coupled receptor 43). In conclusion, gut microbial diversity did not change in essential hypertension, but we observed a significant shift in microbial gene pathways. Hypertensive subjects had lower levels of GPR43, putatively blunting their response to blood pressure-lowering metabolites.